Capillary Blood Levels of Hydroxychloroquine and Methotrexate Are Stable for up to 5 Years When Collected on Volumetric Absorptive Microsamplers. (8th February 2021) - Brady, Kelley; Alexander, Roberta Vezza; Stimson, Deborah; Rudolph, Mark; Kammesheidt, Anja
Abstract: Background: Hydroxychloroquine (HCQ) and methotrexate (MTX) are common antirheumatic drugs used chronically by patients with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) (1, 2 ). Therapeutic drug monitoring (TDM) of HCQ and MTX provides critical compliance information, but typically requires venipuncture and shipment of refrigerated blood samples to the clinical laboratory. Capillary blood collection by finger prick offers a convenient alternative to venipuncture. The long-term stability of capillary blood HCQ and MTX collected using volumetric absorptive microsamplers (VAMS) has not previously been evaluated. In this study, we evaluated the stability of capillary MTX and HCQ levels when stored on VAMS for up to 5 years. Methods: Samples of patients with RA and SLE were collected for HCQ or MTX monitoring as part of 2 clinical studies in 2015 (HCQ: n = 24 | MTX: n = 61) and 2017 (HCQ: n = 126). Venous and capillary blood samples were shipped to Exagen Inc.'s clinical laboratory. HCQ and MTXPG3 were measured using separate LC-MS/MS methodologies. Baseline venous blood levels of HCQ and MTXPG3 were determined within 1 week of draw and compared to capillary blood levels determined following 3 or 5 years of storage. Results: Venous blood HCQ and capillary blood MTXPG3 determinations made at baseline were significantly different from capillary blood determinations performed following 5 years of storage at −80 °C. However, these differences were within the specified limits of agreement [HCQ: Avg % change after storage (CI 95%) = −7.1% (−12.6, −1.6%), pt-test = 0.0205, interclass correlation coefficient (ICC) = 0.96 | MTXPG3 : Avg % change after storage (CI 95%) = 13.3% (7.1, 19.4%), pt-test = 0.0001, ICC = 0.90]. Conclusion: Dried capillary blood HCQ and MTXPG3 levels collected on VAMS are stable for up to 5 years.